Conversation Implicature in Interrogative Utterance of The Discourse of E-Commerce Business Advertisement - Bambang Prastio; Abd. Syukur Ibrahim; Gatut Susanto (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This research aims to describe the function of interrogative utterance contained in conversation implicature in the discourse of e-commerce business advertisement. The source of data in this research was in the form of interrogative utterance obtained in e-commerce business advertisement such as online shopping, online transportation, and drop shipping existed in YouTube. E-commerce advertisement of online shopping is an advertisement which frequently has conversation implicature. Meanwhile, online transportation advertisement and drop shipping seldom have conversation implicature. This research employed pragmatics in order to analyze the transcript data. Based on the data analysis, the researcher found out five functions of interrogative utterance, they are (1) instruction function, (2) asking function, (3) forbidding function, (4) refusing function, and (5) suggesting function. From these five functions of interrogative utterance in the conversation implicature, it can be concluded that the discourse of interrogative utterance in the advertisement of e-commerce leads to persuasive form.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan fungsi ujaran interogatif yang terkandung dalam implikatur percakapan dalam wacana iklan bisnis e-commerce. Sumber data dalam penelitian ini adalah dalam bentuk ucapan interogatif yang diperoleh dalam iklan bisnis e-commerce, seperti belanja online, transportasi online, dan pengiriman drop yang ada di youtube. Iklan e-commerce dari belanja online adalah iklan yang sering memiliki implikatur percakapan. Sementara itu, iklan transportasi online dan layanan dropshipping jarang memiliki implikatur percakapan. Penelitian ini menggunakan pragmatik untuk menganalisis data transkrip. Berdasarkan analisis data, peneliti menemukan lima fungsi ucapan interogatif, yaitu (1) fungsi instruksi, (2) fungsi bertanya, (3) fungsi melarang, (4) fungsi menolak, dan (5) fungsi saran. Dari lima fungsi ujaran interogatif ini dalam implikatur percakapan, dapat disimpulkan bahwa wacana ujaran interogatif dalam iklan e-commerce mengarah pada bentuk persuasif.